Industrial Agroforestry: An ITC initiative - Kulkarni, H. D. (Indian Farming, 2015)
Agroforestry is the future of pulp and paper industry as it not only helps meet the wood demand but also reduce pressure on the natural forest and agricultural land alike for growing pulpwood plantations. Agriculture sector in the country covers about 143 million ha out of which 40 million ha is classified as degraded. Such land when put under Agroforestry can help meet food and wood demand of the country. Thus, agroforestry is agronomically sustainable, environmentally desirable and economically beneficial.